Hypertension in pregnancy as a risk factor for cardiovascular disease later in life - Garovic, Vesna D; Bailey, Kent R; Boerwinkle, Eric; Hunt, Steven C; Weder, Alan B; Curb, David; Mosley, Jr, Thomas H; Wiste, Heather J; Turner, Stephen T (Journal of hypertension, 2010)
The association between hypertension in pregnancy and future cardiovascular disease (CVD) increasingly is recognized. We aimed to assess the role of hypertension in pregnancy as an independent risk factor for hypertension, coronary heart disease (CHD), and stroke later in life. Women who participated in the Phase 2 (2000-2004) Family Blood Pressure Program study (n = 4782) were categorized into women with no history of pregnancy lasting more than 6 months (n = 718), women with no history of hypertension in pregnancy (n = 3421), and women with a history of hypertension in at least one pregnancy (n = 643). We used Kaplan-Meier and Cox proportional hazard models to estimate and contrast the risks of subsequent diagnoses of hypertension, CHD, and stroke among the groups. Women with a history of hypertension in pregnancy, compared with those without such a history, were at increased risks for the subsequent diagnoses of hypertension (50% hypertensive at the age 53 vs. 60, P < 0.001), CHD (14% estimated event rate vs. 11%, P = 0.009), and stroke (12% estimated event rate vs. 5%, P < 0.001). The increased risk for subsequent hypertension remained significant after controlling for race, family history of CVD, smoking, dyslipidemia, and diabetes mellitus, with an adjusted hazard ratio of 1.88 [95% confidence interval (CI) 1.49-2.39, P < 0.001]. After controlling for traditional risk factors, including subsequent hypertension, the increased risk for stroke remained statistically significant (hazard ratio 2.10, 95% CI 1.19-3.71, P = 0.01), but not for CHD. Hypertension in pregnancy may be an independent risk factor for subsequent diagnoses of hypertension and stroke.